Performance evaluation and comparison of switched reluctance cylindrical linear motor - Abdul Shukor , Fairul Azhar; Wakiwaka, Hiroyuki; Tashiro, Kunihisa; Yajima, Hisashi; Kanazawa, Takehiko; Fujiwara, Nobuhiro (2013)
Nowadays, most of the researchers have put a lot of effort in designing the permanent magnet type of linear motor. However, due to resource problem occur recently to the permanent magnet material has led to increment of the material cost. This situation made the linear motor development cost is increase as well. Because of this reason, most of linear motor manufacturers are prefer to development non-permanent magnet type to ensure stability and competitive price. Therefore, in this research, a switched reluctance linear motor was designed. The teeth shape has been varied in order to observed the effect to it’s performance. As a result, the best model of switched reluctance linear motor with optimum teeth shape has been proposed. The performance of the model also has been compared to other similar type of linear motor and the permanent magnet type of linear motor.